EFFECTIVENESS OF POWTOON AS LEARNING MEDIA TO IMPROVE HIGH SCHOOL STUDENTS’ ACCOUNTING LEARNING OUTCOMES - Sheila Erdi El-Majid; Muhammad Khafid; Arief Yulianto (Journal of Economic Education, 2025)
The advancement of information technology has opened new opportunities for innovation in education, including the use of Powtoon as a learning medium. This study aims to examine the effectiveness of Powtoon in improving students’ learning outcomes in accounting at the senior high school level. Using a literature review method, data were collected from various scientific articles and journals, then analyzed through a qualitative descriptive approach. The findings show that integrating Powtoon into the learning process significantly enhances student engagement, motivation, and understanding. Data from multiple studies indicate improvements in learning achievement across affective, cognitive, and psychomotor domains, with an average increase in student performance from 71.85% to 89.22% after using animated media. Additionally, Powtoon effectively accommodates diverse learning styles, particularly for visual learners. In conclusion, Powtoon serves not only as a visual aid but also as a powerful tool to increase learning effectiveness, foster a more interactive classroom environment, and support the holistic development of students in alignment with an independent curriculum. Therefore, Powtoon is strongly recommended as an innovative learning medium for accounting and other subject areas